Pemanfaatan energy baru terbarukan di SMAN 1 Taliwang - Arif - Mulyanto; N. - Nurchayati; Nasmi Herlina Sari; Achmad - Zainuri (Universitas Mataram, 2019)
Energy source of fossil decrease while population , development and technology growth increase, so its important to seek and use renewable energy. The tipically renewable sources for west Nusa Tenggara are solar energy and wind energy. Thess energy are cheap and amount that can developt dan use to reduce of oil demand. Sosialisaton of solar energy dan wind energy is needed. The student, who is continue to developt the nation, will be target as member of sosialisation, especially SMAN 1 Taliwang. The students respon are good and fun indicate that the ssialisation is success. The helpful factor are school contribution and student curiosity to get knowledge of renewable energy. Keywords : renewable energy, solar energy, wind energy